Performance of heterotopic bone elicited with bone morphogenic protein-2 microspheres as a bone repair material - Deyin Kong; Guimei Lin; Yanbin Shi; Zili Gu; Yan Gao; Yihua Feng (Materials & Design, 2020)
Bone defects are a major threat to human health, and heterotopic bone provides advantages that other materials do not provide in the treatment of bone defects. MPEG-PCL microspheres loaded with bone morphogenetic protein-2 (BMP-2/MPEG-PCL-MS) are an emerging means of culturing heterotopic bone. However, the effect of such microspheres on the quality of heterotopic bone osteogenesis has rarely been studied. The performance of heterotopic bone as a bone repair material has also rarely been reported. To explore the effect of microspheres on heterotopic bone osteogenesis and to explore the performance of heterotopic bone in bone repair, we designed compression tests, nanoindentation tests, and a finite element (FE) simulation. The effects of microspheres on the quality of heterotopic bone osteogenesis and performance of heterotopic bone as a bone repair material were evaluated from the mechanical properties, material properties, and FE simulation. The results demonstrate that eight-week heterotopic bone using microspheres has suitable mechanical and material properties, performs well in bone repair FE simulation, and can meet the material requirements of bone repair. Hence, this heterotopic bone as bone repair material has promising potential for clinical applications, and provides a good strategy for combination between tissue engineering and pharmaceutical science.